New deep ocean Iravadiidae of the genus Ceratia (Caenogastropoda: Truncatelloidea) from an underwater canyon and adjacent regions of the southwestern Atlantic (northeastern Brazil) - Lima, Silvio Felipe B.; Júnior, Ivan Cardoso L.; Guimarães, Carmen Regina P.; Dominguez, José Maria L. (Zootaxa, 2016)
Previous studies on the mollusks from Brazilian underwater canyons have addressed the record and description of new species of aplacophorans, bivalves, scaphopods and/or gastropods (Leal & Simone 2000; Absalão 2010; Corrêa et al. 2014). Leal & Simone (2000) described a new bathyal gastropod of the family Pseudococculinidae collected from the continental slope and Doce River Canyon (960 m) off the state of Espírito Santo (southeastern Brazil). Absalão (2010) reported a number of species of gastropods, bivalves and scaphopods from Campos Basin off the state of Rio de Janeiro (southeastern Brazil). It is likely that some of these species reported by Absalão (2010) were collected from underwater canyons in the northern portion of the Campos Basin. Corrêa et al. (2014) recorded two species of aplacophorans of the genus Falcidens Salvini-Plawen, 1968 obtained from the continental slope and underwater canyons of Campos Basin. Certainly more species of mollusks were studied from Brazilian underwater canyons, but not duly mentioned in publications (i.e., the region of canyons may have been referred to as the continental slope or deep sea).